The Discourse of Transformative-Critical Pedagogy Among Modernist Muslims - Mohamad Ali (Universitas Muhammadiyah Surakarta, 2017)
The 1980s is the starting point for the discourse of the transformative-critical pedagogy among Indonesian Muslim scholars. It is Paulo Freire, a Brazilian pedagogue and critical social thinker, who introduces the early idea of transformative-critical and attempts to understand Islam empirically, at once. Initially, this idea exclusively discussed by NGO activists and Catholic clergies. Subsequently, the struggle between transformative-critical pedagogy and transformative Islamic thought generates a new concept known as Transformative Islamic Education (TIE). From a restricted theme among the NGOs, it expands as a discourse among lecturers of higher education. This sociological-based expansion allows modernist Muslims to participate in this litigious intellectual discussion. Ahmad Syafii Maarif, Moeslim Abdurrahman, Abdul Malik Fadjar, Noeng Muhadjir, Mochtar Buchori, Amin Abdullah, Musa Asyari, Abdul Munir Mulkhan, and Said Tuhuleley, to mention some modernist Muslim pedagogues who are renowned in the discussion and implementation of critical pedagogy. Essentially, the discourse of critical pedagogy among modernist Muslims has prompted the possibility of different nuances in defining transformative Islamic education.